(untitled) (Research, Society and Development, 2022)
Cancer is its invasive disease and causes a people’s life and a people’s life. A multiprofessional experience of interruption is necessary, where hospitalization is part, generating an experience of family rupture, providing preliminaries of their family and social interruption process, invasive interventions, in addition to pain. The general objective of this research was to understand the use of fairy tales as a therapeutic resource by the occupational therapist objective, with children and adults hospitalized for cancer treatment. Specific objectives: to identify, during the meetings, the stories of meaning, expressed through reports and/or expressive painting activity; to compare the differences in behavior and similarities in behavior in the meanings brought by and by adults in relation to fairy tales and possible in the same ones during the activity. This is an experience report, within a Hospital in Sergipe for cancer treatment, where meetings were held, in which the activities used fairy tales and expressive. Patients can be seen to make a significant contribution to the occupational therapist using fairy tales, highlighting sick subjects not only as active, but active, reactive beings, who have needs and dreams, in addition to a life story that can be considered. The main difference between children and adults was what children brought in the drawings and correlated the elements of the story that most caught their attention, while adolescents and adults correlated their lives with that tale.